Potent Anti-Inflammatory Activity of Pyrenocine A Isolated from the Marine-Derived Fungus Penicillium paxilli Ma(G)K - Toledo, Thaís Regina; Dejani, Naiara N.; Monnazzi, Luis Gustavo Silva; Kossuga, Miriam H.; Berlinck, Roberto G. S.; Sette, Lara D.; Medeiros, Alexandra I. (Mediators of Inflammation, 2014)
Very little is known about the immunomodulatory potential of secondary metabolites isolated from marine microorganisms. In the present study, we characterized pyrenocine A, which is produced by the marine-derived fungus Penicillium paxilli Ma(G)K and possesses anti-inflammatory activity. Pyrenocine A was able to suppress, both pretreatment and posttreatment, the LPS-induced activation of macrophages via the inhibition of nitrite production and the synthesis of inflammatory cytokines and PGE2. Pyrenocine A also exhibited anti-inflammatory effects on the expression of receptors directly related to cell migration (Mac-1) as well as costimulatory molecules involved in lymphocyte activation (B7.1). Nitrite production was inhibited by pyrenocine A in macrophages stimulated with CpG but not Poly I:C, suggesting that pyrenocine A acts through the MyD88-dependent intracellular signaling pathway. Moreover, pyrenocine A is also able to inhibit the expression of genes related to NFκB-mediated signal transduction on macrophages stimulated by LPS. Our results indicate that pyrenocine A has promissory anti-inflammatory properties and additional experiments are necessary to confirm this finding in vivo model.